CGIAR Gender and Breeding Initiative - Thiele, Graham; Polar, Vivian (International Potato Center, 2018)
Presented by Graham Thiele and Vivian Polar (RTB/CIP), as part of the Annual Gender Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 27-28 September 2018.